2022
DOI: 10.1111/ctr.14628
|View full text |Cite
|
Sign up to set email alerts
|

Does prolonged cold ischemia affect outcomes in donation after cardiac death donor kidney transplants?

Abstract: Background The purpose of this study was to analyze the combined effect of cold ischemia time (CIT) and donation after cardiac death (DCD, with requisite warm ischemia time, WIT) on kidney transplant (KT) outcomes. Methods Single center retrospective review of DCD KT recipients stratified by CIT. Results From 6/08 to 10/20, we performed 446 DCD KTs (115 CIT ≤20, 205 CIT 20–30, 88 CIT 30–40, 38 CIT ≥40 h). Mean WITs (26/25/27/23 min) and KDPI values (59%/55%/55%/59%) were similar while mean CITs (16.4/23.6/33.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Finally, as 40% of the renal transplants performed in the Unite States are DCD renal transplants, alternative, more effective approaches that may improve the function and the overall outcome of "less than optimal graft" are urgently needed. Our transplant program has a broad, longstanding experience in the use of such allografts including DCD kidneys [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] and our patients would see potential benefit from treatments that mitigate DCD kidney damage. Overall, our ex vivo data confirmed the beneficial effects of MITO observed in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as 40% of the renal transplants performed in the Unite States are DCD renal transplants, alternative, more effective approaches that may improve the function and the overall outcome of "less than optimal graft" are urgently needed. Our transplant program has a broad, longstanding experience in the use of such allografts including DCD kidneys [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] and our patients would see potential benefit from treatments that mitigate DCD kidney damage. Overall, our ex vivo data confirmed the beneficial effects of MITO observed in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor, We read with great interest the article by Harriman et al who reported the important association of prolonged cold ischemia and outcomes of kidneys donated after cardiac death. 1 We congratulate the authors on this novel and important finding, and would like to highlight several points. First, the authors definition of warm ischemia time (WIT) corresponds to "donor" WIT, prior to organ retrieval.…”
mentioning
confidence: 90%
“…Cold storage (CS) solutions such as Viaspan are typically used to maintain the viability of deceased donor kidneys [ 5 , 6 , 7 , 8 , 9 ] until a recipient can be chosen. However, a well-known contributing factor to poor graft outcomes is prolonged exposure to CS, and we previously demonstrated in a rat model that CS exacerbates renal injury after transplantation [ 10 , 11 , 12 , 13 ]. After brain death, there is a robust inflammatory response that can damage deceased donor kidneys, which may also contribute to deceased donor graft vulnerability throughout CS [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%